Bamboo : ITS Distribution, Production, Habitat and Agroforestry Potential - Nath, V.; Pal, Rajat S.; Banerjee, S. K. (Indian Forester, 2008)
Bamboo is one of the fastest growing plant species which occurs under varied climatic and edaphic conditions. In the present review the distribution and productivity of different species of bamboo in India have been discussed. The climatic and edaphic conditions suitable for the optimum growth of some important bamboo species have also been described along with bamboo based agro-forestry models.